The power of political parties political participation, clientelism, and remittances in the Dominican Republic - Gonzalez-Acosta, Edward D.; Htun, Mala.; Bach, Jonathan; New School University (Ann Harbor, Mi. ProQuest LLC, 2009)
Political participation is an essential component of democracy. Democracy presupposes that politics is the result of the interaction of parties and voters, where the latter participate in politics to provide the former with the authority to govern and act on their part. But understanding the determinants of political participation is highly important to assess the democratic character, or the normative value, of political participation. For example, I contend that clientelist-inspired participation runs counter to the fundamental tenets of democratic accountability, transparency, and the nature of representative democracy itself. To promote non-clientelist democratic participation, a deeper understanding of the determinants of political participation is needed. The literature on political clientelism claims that increases in individuals' socio-economic status (SES) are sufficient to weaken political clientelism and promote democratic participation. But is this always the case? Can economic development tools alone weaken clientelist-inspired political participation? Or is a more direct institutional approach sometimes needed to promote non-clientelist behavior between parties and voters? My project explores these issues by looking at political participation and clientelism in the Dominican Republic (DR).Overall, my project employs quantitative and qualitative research methods to analyze party-voter relations, political clientelism, and the role of personal resources in determining individuals' political participation in the DR. The results show that SES and other indicators of personal resources and motivations are insignificant factors in determining individuals' political participation in the DR. Furthermore, the results consistently indicate that institutional factors - political affiliation and exposure to political clientelism - are by far more important in shaping individuals' political participation in the DR than personal resources or motivations. Thus, both my qualitative and quantitative data and relevant analyses unfailingly find that the insitutionalist approach to political participation is more appropriate in the Dominican context and accordingly changes in an individuals' personal resources or motivation do not affect their political participation nor weaken political clientelism.
Thesis (Ph.D. Political Science)--New School University
Electronic reproduction.
Keywords: Political participation -- Dominican Republic; Political participation; Dominican Republic -- Politics and government -- 20th century